Intermodal freight transportation - Reis, Vasco; Macário, Rosário (Elsevier, 2019)
Intermodal Freight Transportation conceptualizes intermodal transport as a set of physical, logical, financial and contractual flows, examining the barriers that impact intermodal freight services and the resulting performance variables. The book covers transport modes, agents, supply and demand patterns, key drivers, trends influencing the freight transportation sector, the evolution of supply and logistics chains, and the impacts of technological advancements, such as autonomous vehicles and e-commerce. In addition, the book covers transport agents, such as shippers, freight forwarders, integrators, and customs, as well as the demand for freight transport services and the key properties of goods.Readers will find a variety of new tools for analyzing and building effective transport chains that addresses component technology, information, responsibility, and financing dimension, along with sections on key organizational, regulatory, infrastructure and technological barriers. The book concludes with a look into the future of the freight transport sector